PRODUCTION OF CARBON COMPOSITE NANOFIBERS BASED ON COAL TAR AND TEXTILE CORD - Yermagambet Bolat Toleukhanuly; Kazankapova Maira Kuttybaevna; Nauryzbaeva Asemay Turlangyzy (Academic Scientific Journal of Chemistry, 2020)
The article conducted experiments on the production of carbon nanofibers based on coal tar and textile cord by method electrospinning in a laboratory setup. Carbon nanofibers (CNFs) were obtained from textile cord carbonizate (TC) and coal tar (CT) from the Shubarkol deposit, and polymethylmethacrylate (PMMA) was used as a binder. The elemental composition was determined and the surface morphology of the samples was studied. As a result of energy dispersive X-ray spectroscopy and SEM microscopy, the chemical compositions of the CNF based on TC + PMMA were determined, which amounted to C-82.69%, O-1.72%, Si-0.46%, Al-15.14%, TC + CT + PMMA: C-88.43%, O-4.06%, Al-7.32%, S-0.19%, the diameter of carbon nanofibers ranged from 64.2 nm to 539.3 nm.